В ПОИСКАХ ОБЩИХ ЦЕННОСТЕЙ : ТРОЙНОЙ ПОРТРЕТ ШЕ СТИДЕСЯТНИКОВ (РИММА КАЗАКОВА, АЛЬБЕРТ ЛИХАНОВ, ВАЛЕРИЙ ПЕТРОЧЕНКО В) - Zwonareva, Łoła (Przegląd Rusycystyczny, 2020)
The subject of this paper is the oeuvre of three writers, who debuted in the sixties of the previous century. One of them is a prose writer, the author of books for children and teenagers (Albert Likhanov), remaining two are poets. The author of this paper discusses their oeuvre as well as their lives. Rimma Kazakova died not so long time ago, Pietrochenkov has emigrated thirty years ago and now he lives in Washington, while Likhanov organizes help for children on a large scale. Rimma Kazakova continued the tradition of the Silver Age. Her poetics referred to the impressionism. She cultivated the poetry of philosophy and love, judged by many as feminist. Her works define, peculiar to the end of fifties, ethical quests as well as negation of pathos and propaganda. The author calls Albert Likhanov a man who always swam against the tide. Since the sixties, as a journalist he wrote about children and education`s problems. Currently he popularizes reading in Russia, writes scholarly works in the field of pedagogy, sets up journals for children, and devotes to the youngest his novels and short stories (e.g. Nobody, Broken Doll). Likhanov is the supporter of ethical values to a large extent shaped by the Eastern Orthodox Church. The poet Valery Pietrochenkov devotes his works to Russia and its culture, first of all to the Petersburg – his home town. His poetry refers to traditional pictures of Russian and world-wide culture and history. His heroes are strong people who stand against the evil – „saint old men” of the Orthodox Church, and great literary authors. The three of presented authors (less known “shestidiesatniki”) connect humanistic and ethical dimension of their writing and Christian values to which they headed for many years.